Analisis Kuantitatif Kadar Kuersetin Pada Fraksi n-Butanol Biji Kakao (Theobroma cacao L.) Dengan Metode Kromatografi Lapis Tipis (KLT) Densitometri - Arbi, Putu; Chandra Wibawa, Agung Ari; Ika Pramitha , Dewa Ayu (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2025)
Cocoa beans (Theobroma cacao L.) are rich in flavonoids that exhibit antioxidant, antidiarrheal, antibacterial, anti-inflammatory, and antidiabetic activities. Quercetin is one of the marker compounds commonly used in the quantification of flavonoid compounds in natural materials. This study aimed to determine the quercetin content in the n-butanol fraction of cocoa bean extract using the thin-layer chromatography (TLC) - densitometric method. Extraction was performed by maceration with 96% ethanol, yielding 118 g, followed by fractionation using n-butanol to obtain 7 g. The mobile phase consisted of toluene:ethyl acetate:formic acid (4:3:0.4). Based on curve calibration of quercetin standard produced a regression equation of y = 0.000016x + 0.0014 with a correlation coefficient (r) of 0.9882. The mean quercetin content in the n-butanol fraction was 0.115 ± 0.039 mg/100 g with a relative standard deviation. The TLC spots exhibited Rf values averaging 0.55, consistent with the quercetin standard. These findings indicate that the n-butanol fraction of cocoa bean extract contains quercetin. The presence indicate n-buthanol fraction contain of quercetin as flavonoid composition of cocoa beans, supporting their potential use as a natural antioxidant source in traditional medicine formulations.